Hubungan Food Tabo dan Lila Ibu Saat Hamil dengan Kejadian Stunting pada Balita Usia 1–24 Bulan Diwilayah Kerja Puskesmas Biromaru Kabupaten Sigi - Marcindy Clarita Reppa; Nurdiana Nurdiana; Nuristha Nuristha (Lembaga Pengembangan Kinerja Dosen, 2025)
The first 1000 days are often referred to as the window of opportunities or the golden period, based on the fact that from the fetal stage to the age of two years, there is a period of rapid growth and development that does not occur in other age groups. Meeting nutritional needs during the first 1000 days of a child's life is very important. This study analyzes the relationship between food taboos and LILA in pregnant women with the incidence of stunting in toddlers aged 1-24 months in the working area of the Biromaru Community Health Center in Sigi Regency. The research design used was a case-control study. The independent variables in this study were food taboos and maternal weight during pregnancy. The dependent variable was stunting in children aged 1-24 months. The population in this study consisted of all mothers who had children with stunting, totaling 32 people. The results of the study show that of the 16 stunted respondents, 11 (34.4%) respondents had food taboos and 5 (15.6%) respondents did not have food taboos. Then, out of 16 non-stunted respondents, 4 (12.5%) respondents had food taboos and 12 (37.5%) respondents did not have food taboos. Meanwhile, out of 16 stunted respondents, 10 (31.3%) respondents had KEK and 6 (18.76%) respondents did not have KEK. Then, of the 16 respondents who were not stunted, 3 (9.4%) respondents had KEK and 13 (40.6%) respondents did not have KEK. There is a relationship between food taboos and the incidence of stunting in children aged 1-24 months (p = 0.001), as well as a relationship between maternal height during pregnancy and the incidence of stunting in children aged 1-24 months (p = 0.01). It is hoped that the Biromaru Community Health Center will increase routine visits and provide education and counseling for mothers and infants.